Howard Fast’s American Revolution - York, Neil (American Studies, 2009)
Howard Fast wrote his novels about the American Revolution to educate what he feared was an ignorant public. He used individuals as archetypes to tell the story of common folk whose lives would otherwise remain lost because of the limited historical record. Believing that he could tap into universal aspects of the human condition he sometimes did careful research before writing, and sometimes did little at all. He claimed to tell truths that transcended any documentary source and wrote with a passion that millions of readers found appealing. His invention of characters, dialogue, and scenes to dramatize real events provide important commentary on the larger problem of fictionalizing the past.